Assessing Student Attitudes Toward Sexual Assault by Using a Mock Trial. Issue 1 (2nd January 2019) - Stichman, Amy J.; Wood, McKenzie; Watson, Anna-Alicia
Abstract : Despite the prevalence of sexual assault on college campuses, college students' views regarding rape continue to be an understudied area. Using criminal justice and sociology students who either attended a mock sexual assault trial or viewed the trial video in their class, this study examined students' attitudes toward rape and rape myth acceptance. Surveys assessed what students believed the verdict should be and why, along with questions surrounding rape myths and beliefs regarding women. Results indicate that female students were more likely to find the defendant guilty. None of the attitudinal variables or plans to work in the criminal justice system, however, had an effect on the verdict. Multiple factors such as gender, race, and hostility toward women influenced attitudes regarding rape myths. These findings suggest that attitudes may be less important when determining sexual assault defendants' guilt than the facts of the case. Policy implications are discussed.